Soil Bacterial Community Structure in Different Micro-Habitats on the Tidal Creek Section in the Yellow River Estuary - Wang, Zhikang; Yang, Kaixin; Yu, Junbao; Zhou, Di; Li, Yunzhao; Guan, Bo; Yu, Yang; Wang, Xuehong; Ren, Zhonghua; Wang, Wei; Chen, Xin; Yang, Jisong (Frontiers in Ecology and Evolution, 2022)
Tidal creeks have attracted considerable attention in estuary wetland conservation and restoration with diverse micro-habitats and high hydrological connectivity. Bacterial communities act effectively as invisible engines to regulate nutrient element biogeochemical processes. However, few studies have unveiled the bacterial community structures and diversities of micro-habitats soils on the tidal creek section. Our study selected three sections cross a tidal creek with obviously belt-like habitats “pluff mudflat – bare mudflat – Tamarix chinensis community – T. chinensis - Suaeda salsa community – S. salsa community” in the Yellow River estuarine wetland. Based on soil samples, we dissected and untangled the bacterial community structures and special bacterial taxa of different habitats on the tidal creek section. The results showed that bacterial community structures and dominant bacterial taxa were significantly different in the five habitats. The bacterial community diversities significantly decreased with distance away from tidal creek, as well as the dominant bacteria Flavobacteriia and δ–Proteobacteria, but in reverse to Bacteroidetes and Gemmatimonadetes. Moreover, the important biomarkers sulfate-reducing bacteria and photosynthetic bacteria were different distributions within the five habitats, which were closely associated with the sulfur and carbon cycles. We found that the bacterial communities were heterogeneous in different micro-habitats on the tidal creek section, which was related to soil salinity, moisture and nutrients as well as tidal action. The study would provide fundamental insights into understanding the ecological functions of bacterial diversities and biogeochemical processes influenced by tidal creeks.